(untitled) (Bangladesh Journal of Child Health, 2025)
Background: The neonatal mortality is still significantly high in Bangladesh. One of the major risk factors for morbidity and mortality in the first 28 days of life is neonatal hypothermia. Hypothermia is a risk factor for neonatal sepsis, intraventricular haemorrhage, necrotizing enterocolitis, respiratory distress, hypoglycemia, metabolic acidosis, hyperbilirubinemia, scleroderma, DIC and pulmonary haemorrhage. Objective: To find out the association between neonatal hypothermia at admission with mortality and morbidity. Methodology: This prospective observational study was conducted in Department of Neonatology in Bangabandhu Sheikh Mujib Medical University over a period of one year from July 2021 to June 2022. Temperature was measured in axilla using commercially available Digital Axillary Thermometer (Elite Digital Thermometer). Study population was divided into normothermic (84) and hypothermic (84) group. The babies were followed up until discharge or death, whichever came first. The primary outcome in this study was neonatal mortality and morbidity. Results: Among the total study population of 497 newborns, frequency of hypothermia was 18.90%. Outborn babies significantly suffered from hypothermia (p=0.021). Early Onset Neonatal Sepsis, Late Onset Neonatal sepsis, shock and hospital stay were significantly higher in hypothermic group than normothermic group (p= 0.03, <0.001,0.002 and 0.001 respectively). Death rate was significantly higher in hypothermic group (p<0.001). More respiratory support were required in hypothermic group compared to normothermic group (p=0.049). Multivariate analysis of hypothermia related mortality and morbidities showed, statistically significant higher rate of late onset neonatal sepsis, shock, prolonged hospital stay (³7 days) and mortality among the hypothermic neonates. Conclusion: Frequency of admission hypothermia is 18.9%. Hypothermia is more common in outborn babies. Late onset neonatal sepsis, shock, prolonged hospital stay and mortality are significantly more common in hypothermic newborns. BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 162-170